Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Negeri Sipil (Studi Kasus Pada Dinas Tenaga Kerja Dan Transmigrasi Provinsi Jawa Barat) - Dita Aditya Rahmawati; Alini Gilang (Jurnal Computech & Bisnis (e-Journal), 2017)
Human resources (HR) is one of the important assets of the company. Human is an important factor in achieving the targets or goals the agency / company. The programs planned by the company an implementation of the vision and mission of the institution. In order to be sustainable, it must be ensured that the program can be applied either by the offender institution. The percentage achievement of performance at the Department of Labor and Transmigration of West Java Province as a whole can be categorized as very good because it can achieve the target of more than 100% and has increased every year even though there are still some elements that have not been able to achieve the targets. Success or failure of purpose agencies / companies are realized can be seen from the process and the factors that affect the performance of employees one of which is the motivation to work. The purpose of the research is to know how to influence employee motivation consists of the intensity, direction and persistence on the performance of the Civil Service in the Department of Labor and Transmigration West Java Province. This research is a quantitative with descriptive analysis techniques causal, classic assumption test, simple linear regression, hypothesis testing partially (t test) and the coefficient of determination. Analysis of the data used is Non-Probability Sampling methods saturated samples. Respondents were used in this study were 110 people. The results showed that motivation high value with test results the coefficient of determination (R2) of 0.348. It can be concluded that the effect of work motivation on the performance of 34.8%, while the remaining 65.2% is influenced by other variables not examined in this study.  Keywords: work motivation, performance, government employees.